Efforts to improve self-concept with adolescent therapeutic group therapy (TKT) and assertive training (AT) for 7th grade students at SMP Negeri 20 Pekanbaru City - Usraleli Usraleli; Erni Forwaty; Fadilah Amimi; Elia Reski Naya; Nanda Azalea (Universitas Muhammadiyah Magelang, 2022)
Adolescents frequently experience social changes that lead to issues, when they start building relationships with people of the same sex as well as those of the opposite sex in order to gain recognition, self-identity and social behavior. Lack of self-confidence, low self-esteem, shyness, anxiety, and hesitancy in expressing opinions are symptoms that appear in adolescents. They also only being silent when given the opportunity to ask questions during the learning process in class or outside of it, and difficulty saying no to things they don't like. One could say that these students have poor or negative self-concept. Through the application of Adolescent Therapeutic Group Therapy (TKT) and Assertive Training (AT), this community service seeks to enhance students' self-concept in the 7th grade at SMPN 20 Pekanbaru. This program is in the form of applying the Therapeutic Group Therapy (TKT) for adolescents and Assertive Training (AT) which is carried out through describing, modeling, role playing, feedback, and transferring. Pre-test and post-test procedures were used before and after the application of Adolescent Therapeutic Group Therapy and Assertive Training (AT). It was known that 26 students were categorized as having a high self-concept at pre-test, and that number rose to 32 at the post-test.